Rip current simulation on some beaches in coastal Quang Nam province - Cong, Nguyen Chi; Mau, Le Dinh; Tuan, Nguyen Van; Dung, Nguyen Thi Thuy; Bac, Phan Thanh; Hoan, Pham Sy; Binh, Tran Van (Vietnam Journal of Marine Science and Technology, 2019)
This paper presents modelling results of rip currents on the main beaches along coastal Quang Nam province including Ha My, Binh Minh, Tam Thanh and Rang beaches during two typical wind seasons: Northeast monsoon (Northeast wind direction, wind levels: 4, 5, 6) and Southwest monsoon (Southeast wind direction, wind levels: 4, 5) using Mike 21 model. Calculation results show that during the Northeast monsoon, the rip current formed in all beaches. In the scenario of level 4 of wind speed, average rip speed was about 40–50 cm/s. In particular, at Tam Thanh beach area, the rip was a typical one with the components such as feeder current, rip neck and rip head. With the level 5 of wind field, the formation of the rip was clearer, the speed of the rip was stronger, average value was about 50–60 cm/s. Meanwhile, with the level 6 of wind field, the typical rip structure was broken, creating local eddies or longshore currents at some positions, but strengthened at other positions. During the Southwest monsoon, the rip current did not form at the beaches and the longshore currents were dominant.